Research on Strategies for Building the Professional Competence of Teaching Administrators in Universities in the New Era - Chen, Qiujin (Education Insights, 2026)
As higher education enters a critical phase of high-quality development and connotative construction in the new era, the digital transformation of education, the implementation of the fundamental task of fostering virtue through education, and the advancement of modernized educational governance have set brand-new standards for the professional competence of university teaching administrators. As core actors responsible for teaching operation, quality control, and the implementation of teaching reforms in universities, the professionalization of teaching administrators directly determines the quality of talent cultivation and the core competitiveness of university schooling. At present, teaching administration teams in domestic universities generally face practical challenges, including outdated professional philosophies, unbalanced competence structures, insufficient digital literacy, incomplete training systems, and inadequate incentive mechanisms. Based on the reform context of higher education in the new era, this paper defines the core dimensions of professional competence for teaching administrators, systematically analyzes the dilemmas in team development, and proposes systematic and actionable capacity-building strategies from five distinct perspectives: philosophy reshaping, tiered training, institutional improvement, digital empowerment, and career support. By addressing these critical gaps, this research aims to cultivate a highly professional, career-oriented, and interdisciplinary team of teaching administrators. Furthermore, it provides essential theoretical references and practical pathways for improving the overall quality and efficiency of university educational governance, thereby advancing the sustainable and connotative development of higher education globally.